(untitled) (Comparative & International Education Series, 2021)
The COVID-19 pandemic has created health, economic, and social crises globally and the rapid spread of the virus has hit the higher education sector hard with disrupting traditional academic programs and campus life. As Higher Education Institutions (HEIs) grapple with these unprecedented challenges, they must realize that they can play a major role in finding and implementing solutions given their expertise in different fields and scientific capacity. International collaboration between governments, non-governmental organizations, business and other societal actors can be one of those strategies to consider. As such, this chapter investigates opportunities and challenges for global collaborations between HEIs and various stakeholders. We argue whether the COVID-19 situation will serve as an impetus for triggering innovative and sustainable global collaborations as a global solution. How to cite this chapter: Minaeva, E., & Marinoni, G. (2022). Global collaboration for global solution in academia opportunities and challenges. In R. Ammigan, R. Y. Chan, & K. Bista, (eds), COVID-19 and higher education in the global context: Exploring contemporary issues and challenges (pp. 172-184). STAR Scholars. https://starscholars.org/product/covid-19-and-higed/